A STUDY OF ANTHROPOMETRIC VARIABLES AND KINESTHETIC SENSE BETWEEN BASKETBALL AND HANDBALL PLAYERS - Khan, Anis Ahmed (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The domain of sports and athletics has evolved significantly over time, achieving numerous milestones due to continuous advancements and their practical applications in the field. Scientific research has played a crucial role in enhancing sports performance, contributing to the development of innovative training methodologies, refined techniques, and strategic execution. These scientific interventions have enabled athletes to push the boundaries of excellence and achieve remarkable success in various sporting disciplines. The present study aimed to examine the differences in anthropometric measurements and kinesthetic sense among state-level basketball and handball players in Maharashtra. A total of 50 athletes, comprising 25 state-level basketball players and 25 state-level handball players, were selected for the study. The key variables analyzed included arm length, leg length, waist girth, calf girth, and kinesthetic sense. The findings of the study revealed that there was no statistically significant difference in calf girth between basketball and handball players. However, significant differences were observed in arm length, leg length, waist girth, and kinesthetic sense between the two groups. These results highlight the distinct physical and sensory attributes associated with each sport, emphasizing the impact of sport-specific demands on an athlete’s physical development.